Gestão, tecnologias e saúde mental na universidade - Amorim, Cibelle dos Santos Carlos (Universidade Federal Rural do Semi-Árido, 2021)
This dissertation is the result of an analysis of how managers at the Federal Rural University of the Semi-Arid (UFERSA) organize their cognitive actions related to the promotion of mental health care. This is a qualitative study that seeks to produce an exploratory analysis, based mainly on the theories of the Biology of Knowledge by Humberto Maturana and on the theory of enactment by Francisco Varela, regarding the way of observing and explaining a phenomenon from the start. of a research experience that involves participants' self-narratives and document analysis. The author, when experiencing work as an administrative technique at the university, activates the sensitive in relation to the circumstances of illness in the social and thematizes management in previous training in production engineering, starts from the following research question: How managers( a) at the Federal Rural University of the Semi- Arid (UFERSA) organize their cognitive actions and integrate technologies aimed at promoting mental health in higher education? Immersed in the scenario of serious crises we are experiencing - health, socio-political and collective mental illness in our country -, the research presents itself as a way to contribute to strengthening knowledge and knowledge about mental health in the context of the experience of university management and, in this direction, broaden the understanding of how we live with our daily behaviors. The theme of mental health, when referring to the context of the management experience, gains power and relevance. The study is dedicated to reflecting on how we are dealing with mental health at the university and which technologies are used, when the purpose is to pay attention to the subjective dimension that constitutes us as human beings. We were able to integrate in the research work the reading and analysis of documents that favor a closer approximation with the actions in progress at the University. We use the first-person methodology proposed by Francisco Varela and collaborators, in the form of intervention research. Theoretical intercessors involve, by highlighting concepts operating for the analysis, among other scientists, those that are very important for our reflection: Humberto Maturana and Francisco Varela, with reflection on the movements of cognition, especially the concepts of - conversation networks, natural drift - conservation and structural change - ; Gilbert Simondon, physicist and philosopher who brings the expanded concept of - technologies -, with his studies that interconnect technologies with the processes of psychic and collective individuation; Nise da Silveira, with her life and work dedicated to proposing a method to promote mental health care, with an emphasis on the concepts of catalyzing affection, everyday space and sensitive time. The empirical field of investigation is UFERSA and the invited participants are managers who work in the various administrative instances of the University at Campus Headquarters, located in the city of Mossoró - RN. The main focus of the investigation was to monitor the actions related to mental health care and, in the sensitive listening of self-narratives, to identify markers that emerged as important and recurrent in the participants' constructions. We followed as markers in this qualitative and exploratory analysis, mainly, the questions that the participants asked themselves when reflecting on the experience of mental health care at the university. A variety of information sources make up this mapping and subsidized the analysis: the filming of the meetings and listening to self-narratives, the transcription of the recordings made and the analysis of a set of documents related to the management and projects of mental health promotion at the University. We were also able to identify the management technologies present in the daily life of UFERSA and the technologies and propositions aimed at promoting mental health care. Participants were able to indicate practices needed to be expanded in the academic context, expressing the weaknesses and forms of illness present and that interact with the sociopolitical and health context. The research clarifies, among other issues: the need for institutional support in the flow of daily decisions that are important in the work of implementing care-oriented technologies; search for support for moments of reflection by the management itself on how they are living and acting in the context of the pandemic, and also how they will be preparing and building modes of action in the circumstances of the postpandemic; desire to improve integration between different collectives and institutional practices aimed at mental health care. It is important to emphasize the emphasis on the search for institutional support in the decision-making processes of managers, when they wish to expand mental health care actions. Among so many learnings, the participants' journey through selfnarratives, interacting with the reading of documents and projects, allowed us to understand that the cognitive actions in progress at the University point to weaknesses in the face of the need for dialogue between all instances, so that they can be built and applied care technologies, supported by ongoing policies for the promotion of mental health
Keywords: Gestão; Universidade; Saúde mental; Tecnologias do cuidado; Ensino Superior; Management; University; Mental health; Technologies of care; Higher Education; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES